Pendampingan Belajar Menggunakan Model Pembelajaran Kooperatif Tipe Make A Match di SD Negeri 1 Selaawi Kecamatan Pasawahan - Adinda, Meisya; Kurniasih, Nunung; Ahmadiah, Didih (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study examines the application of the Make A Match cooperative learning model in learning assistance at SD Negeri 1 Selaawi, Pasawahan District, Purwakarta Regency. The primary goal of this program is to enhance students' learning motivation in Islamic Religious Education (PAI). The research employs the Participatory Action Research (PAR) method, engaging first-grade students in interactive learning activities using question-and-answer cards to match learned concepts. The results indicate that this approach effectively increases students' active participation and enthusiasm. Out of 29 students, 27 stated that this learning method was enjoyable. Thus, the Make A Match model has been proven to enhance student engagement in learning while providing a more enjoyable and interactive learning experience.